Análise da evolução da paisagem no entorno da represa dos rios jaguari e jacareí, estado de são paulo, com base em sensoriamento remoto e SIG - de Oliveira, Paulo Eduardo (2008)
The primary objective of this study is to evaluate by means of remote sensing and GIS, the landscape evolution around the Jaguari and Jacareí River Dam, located in the eastern section of the State of São Paulo, Brazil. For this purpose we used LANDSAT 5/YM and CBERS-2/CCD images from 1984/1985 and 2006, respectively, considering the following classes of land use: forest, cultivated forest, agriculture, urban areas and water bodies. The two selected dates reflect important changes in the region such as the installation of the dam and subsequent urbanization of parts of its margins and the enlargement of the Fernão Dias Federal Highway, which contributed to an increase of areas of anthropic activities in the studied region. The results also indicate an increase in areas covered by native and planted forests, thus confirming a similar trend in other areas of the State of São Paulo.